Adjoint sensitivity analysis of the T, , and L types of microstripline low noise amplifiers - Demirel, Salih; Gunes, Filiz; Mahouti, Peyman (WILEY, 2017)
In this work, the sensitivities of the Gain G(T), noise figureF, magnitudes and phases of the input (in) and output (out) reflection coefficients of low noise amplifier are carried out analytically with respect to the matching mirostrips' widths and lengths depending upon the position and the configuration types, using adjoint network method via wave approach for different types of matching networks. Thus, not only these analytical gradient expressions can be implemented with either the gradient-based or non-gradient optimization algorithms even simple metaheuristic algorithm for a high-speed and improved design of the microstrip amplifiers but at the same time the tolerance limitations of the designs can be provided depending on type of the matching network. As a case study, performance sensitivities of the T, , L types of microstrip low noise amplifier with the design target parameters of G(Tmax), F-min and |(in)|=0.3 with the operation bandwidth of 10-18GHz are worked out and compared with results of the numerical perturbation and chain sensitivity matrix methods. Furthermore, performance sensitivity characteristics of the microstrip lines for all types of amplifier circuits are given, and comparisons are made among microstrip lines at the same positions along the operation bandwidths. Copyright (c) 2015 John Wiley & Sons, Ltd.
Keywords: adjoint network; wave approach; transducer gain; noise figure; input and output reflection coefficient; MICROWAVE TRANSISTOR; LIMITATIONS; NETWORK; DESIGN; Engineering; Mathematics